Observing the three-dimensional terephthalic acid supramolecular growth mechanism on a stearic acid buffer layer by molecular simulation methods. Issue 3 (8th January 2020) - Su, Chia-Hao; Chen, Hui-Lung; Sun, Shih-Jye; Ju, Shin-Pon; Hou, Tsu-Hsun; Lin, Che-Hsin
Abstract : The terephthalic acid (TPA) supramolecular growth mechanisms on the stearic acid (STA) buffer layer, such as the phase separation and layer-by-layer (LBL) mechanisms, were considered by molecular simulations. Abstract : The terephthalic acid (TPA) supramolecular growth mechanisms on the stearic acid (STA) buffer layer, such as the phase separation and layer-by-layer (LBL) mechanisms, were considered by molecular simulations. The electrostatic surface potential (ESP) charges obtained by the semi-empirical ab initio package VAMP with PM6 were used with the Dreiding force field. The stochastic tunneling-basin hopping-discrete molecular dynamics method (STUN-BH-DMD) was first used to construct the most stable STA buffer layers (STA100, STA120, and STA140) on graphene. At STA100 and STA120, the STA molecule stacking along their long axis is the major mechanism to obtain the stable STA buffer layer. At STA140, the hydrogen bond network between the terminal COOH groups of STA molecules makes the STA buffer layer the most stable, leading to a higher disintegration temperature among all STA coverages. In the early growth of the TPA supramolecule, TPA molecules were first adsorbed by the holes between STA piles. At STA100 and STA120, the subsequent TPA molecules were adsorbed by the TPA molecules within the holes, leading to the phase separation growth. At STA140, the TPA supramolecule tends to grow by the LBL mechanism.